Correspondence, newspaper cuttings, photographs, notes and typescript speeches relating to the Liam Lynch annual commemoration ceremony - O'Donoghue, Florence, 1895-1967; Twomey, Moss, 1896-1978; Whelan, Patrick, 1890-1986; Neenan, Cornelius F., 1894-1979; Córas Iompair Éireann (1955)
Correspondents include Moss Twomey, Pax Whelan, Con Neenan, and Coras Iompair Éireann relating to running a special train for the commemoration. Includes a draft speech by Moss Twomey.
Keywords: O'Donoghue, Florence, -- 1895-1967 -- Correspondence; Lynch, Liam, -- 1893-1923; Ireland -- History -- 1922-